2015
DOI: 10.4103/0259-1162.150157
|View full text |Cite
|
Sign up to set email alerts
|

Comparison between two different selective spinal anesthesia techniques in ambulatory knee arthroscopy as fast-track anesthesia

Abstract: Background:There were several studies using either low dose Bupivacaine as unilateral selective spinal anesthesia (SSA) or low dose lidocaine SSA for ambulatory knee arthroscopy. There were many concerns about high failure rate, complications, and different times to home readiness discharges.Aim of the Study:The study aimed to: (1) Compare the clinical efficacy and side effects of two different techniques of SSA in subarachnoid block for ambulatory knee arthroscopy (2) evaluate the possibility of a shorter sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
9
1
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 18 publications
1
9
1
3
Order By: Relevance
“…The full-text of 123 articles were evaluated, and then, 84 articles were excluded due to the following reasons: no results about the incidence of TNS (n = 42); no other local anesthetics were used (n = 18); conference posters (n = 7); abstracts only (n = 4); protocols (n = 4); healthy subjects (n = 4); non-randomized studies of intervention (n = 2); different anesthetic techniques between groups (n = 1); mixed spinal anesthetics (n = 1); and a brief report (n = 1). Therefore, a total of 39 RCTs were included in the final analysis ( Figure 1) [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18].…”
Section: Descriptions Of Trialsmentioning
confidence: 99%
See 1 more Smart Citation
“…The full-text of 123 articles were evaluated, and then, 84 articles were excluded due to the following reasons: no results about the incidence of TNS (n = 42); no other local anesthetics were used (n = 18); conference posters (n = 7); abstracts only (n = 4); protocols (n = 4); healthy subjects (n = 4); non-randomized studies of intervention (n = 2); different anesthetic techniques between groups (n = 1); mixed spinal anesthetics (n = 1); and a brief report (n = 1). Therefore, a total of 39 RCTs were included in the final analysis ( Figure 1) [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18].…”
Section: Descriptions Of Trialsmentioning
confidence: 99%
“…More subsequent studies evaluating the effect of lidocaine on the risk of TNS have been published [2,3]. Furthermore, among them, many studies reported no patients suffering from TNS after spinal anesthesia with lidocaine [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18]. Therefore, it is still controversial on the safety of lidocaine for spinal anesthesia during ambulatory surgery in terms of TNS.…”
mentioning
confidence: 99%
“…Bu komplikasyonlardan karşımıza en çok çıkanlardan olan postoperatif baş ağrısı, idrar retansiyonu, bel ağrısı; cerrahi pratiğinde bizleri en çok zorlayan sonuçlardandır. 7,8,9 Postdural ponksiyon baş ağrısı (PDPB) duradaki herhangi bir yaralanma sonucu ortaya çıkar. Tipik olarak bilateral, frontal veya retroorbital, oksipital ve enseye doğru uzanan tarzdadır.…”
unclassified
“…Başlaması genellikle 12-72 saat sonradır, ancak daha erken de ortaya çıkabilir. 7,8,9,10,11,12,13,14 Dural defektten kaçış sonucu oluştuğuna inanılır. Kan damarları üzerinde yüksek çekilme ağrıya katkıda bulunur.…”
unclassified
See 1 more Smart Citation